Poverty Reduction Evaluation Through the Program Looks Down on Poverty Problems (Gertak) in Trenggalek District, East Java - PURNAWATI, Laily; ANGKASAWATI, Angkasawati; WAHYUDI, Andri (International Journal of Environmental, Sustainability, and Social Science, 2023)
Poverty is a problem faced in all regions in Indonesia as well as in the Trenggalek district. To overcome this poverty problem, the Trenggalek district government has one breakthrough, namely by changing the paradigm from just a program to a poverty alleviation movement abbreviated as GERTAK. Because overcoming poverty cannot only be done by providing aid programs but the most important thing is to change the thinking of these poor people themselves so that they are willing and able to change. To research poverty reduction evaluation in the Trenggalek district, a qualitative descriptive approach was used. Data sources are obtained by direct observation of the field and interviews with predetermined sources. The validity of the data is obtained through the triangulation method. The results obtained that poverty reduction through the GERTAK program can be felt and accepted by the community. Although in its implementation there are still obstacles such as changing regulations and still low awareness of the poor themselves.